2022
DOI: 10.1002/chem.202201114
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Long Lived Luminescent Triplet Excited States in Cyclic (Alkyl)(amino)carbene Complexes of Zn(II) Halides

Abstract: The high element abundance and d10 electron configuration make ZnII‐based compounds attractive candidates for the development of novel photoactive molecules. Although a large library of purely fluorescent compounds exists, emission involving triplet excited states is a rare phenomenon for zinc complexes. We have investigated the photophysical and ‐chemical properties of a series of dimeric and monomeric ZnII halide complexes bearing a cyclic (alkyl)(amino)carbene (cAAC) as chromophore unit. Specifically, [(cAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 73 publications
2
26
0
1
Order By: Relevance
“…One of the most recent fundamental developments concerning photoactive Zn II compounds pursues the idea to introduce other emission types than ligand-based fluorescence, for example, states with triplet and/or charge-transfer character in halide complexes. To date, this specific research thrust seems to concentrate largely on the solid state, presumably because phosphorescence and charge-transfer emission are trickier to obtain in fluid solution at room temperature. The solution phase is however very relevant for photoactive triplet and charge-transfer excited states, due to possible applications in triplet energy-transfer catalysis, triplet–triplet annihilation upconversion, photoinduced electron transfer, and photoredox catalysis, including perspectives for solar energy conversion .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent fundamental developments concerning photoactive Zn II compounds pursues the idea to introduce other emission types than ligand-based fluorescence, for example, states with triplet and/or charge-transfer character in halide complexes. To date, this specific research thrust seems to concentrate largely on the solid state, presumably because phosphorescence and charge-transfer emission are trickier to obtain in fluid solution at room temperature. The solution phase is however very relevant for photoactive triplet and charge-transfer excited states, due to possible applications in triplet energy-transfer catalysis, triplet–triplet annihilation upconversion, photoinduced electron transfer, and photoredox catalysis, including perspectives for solar energy conversion .…”
Section: Introductionmentioning
confidence: 99%
“…In light of current developments in photoactive d 10 metal complexes, we were therefore interested in studying the effect of different diborene and metal substituents as well as the nature of the metal center on the photostability and emissive properties of diborene coinage metal π complexes, in the hope of enhancing ISC and making phosphorescence from the T 1 state accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the propensity of MLCT states is low in Zn­(II). Formerly investigated zinc complexes mainly showed prompt fluorescence and only a few were reported to be phosphorescent. A recent re-investigation of the photophysical behavior of zinc­(II) diimine bis-thiolate complexes revealed that their room-temperature LLCT emission actually shows TADF characteristics . With regard to lighting applications, Zn­(II) complexes were mostly employed as fluorescent emitters or hosts for fluorescent and phosphorescent dopants. The growing interest in new TADF-based OLED emitters strongly promoted research on Zn­(II) emitters.…”
Section: Introductionmentioning
confidence: 99%